2021
DOI: 10.1159/000520934
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Number of Urodynamics in Urological and Gynaecological Clinics Reflects Decreased Importance for Surgical Indications: German Population-Based Data from 2013 to 2019

Abstract: <b><i>Introduction:</i></b> The routine use of urodynamic studies (UDS) has been questioned. Additionally, the material and personnel costs are poorly remunerated. We aimed to analyse the UDS utilization in Germany. <b><i>Methods:</i></b> We analysed UDS performed by hospitals based on quality reports from 2013 to 2019. A representative sample of 4 million insured persons was used to estimate outpatient UDS utilization from 2013 to 2018. <b><i>Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a 12-year follow-up study after a tension-free vaginal tape procedure, a VLPP < 60 cm H 2 O was the only independent predictor of recurrence. However, the biggest obstacle in the determination of ALPP is the need for an invasive urodynamic study (UDS), which appears to be used less frequently to evaluate SUI due to cost, personal shortage, or other reasons [19]. According to previous research, the SEST has been suggested as a noninvasive and low-cost alternative to UDS in the prediction of ALPP; however, the results are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…In a 12-year follow-up study after a tension-free vaginal tape procedure, a VLPP < 60 cm H 2 O was the only independent predictor of recurrence. However, the biggest obstacle in the determination of ALPP is the need for an invasive urodynamic study (UDS), which appears to be used less frequently to evaluate SUI due to cost, personal shortage, or other reasons [19]. According to previous research, the SEST has been suggested as a noninvasive and low-cost alternative to UDS in the prediction of ALPP; however, the results are conflicting.…”
Section: Introductionmentioning
confidence: 99%